Physiological mechanism underlying spikelet degeneration in rice - Zhi-qin WANG; Wei-yang ZHANG; Jian-chang YANG (Journal of Integrative Agriculture, 2018)
The phenomenon of degenerated spikelets is very common in cereals, and considered as a serious physiological defect and a main constraint to grain production. Understanding the physiological mechanism in which spikelet degeneration occurs would have great significance in enhancing yield potential in grain crops. Taking rice as an example, the paper reviewed the physiological mechanism underlying spikelet degeneration, with focus on the roles of phytohormones in regulating the process. There are several hypotheses for the spikelet degeneration, such as resource limitation, self-organization, and primigenic dominance. However, convincing evidences are not enough to support the assumptions. Phytohormones including auxins, cytokinins, gibberellins, abscisic acid, and ethylene are involved in regulating spikelet degeneration in cereals. The new phytohormones of brassinosteroids and polyamines have been observed to suppress spikelet degeneration in rice. The interactions among or between plant hormones may play a more important role in regulating spikelet degeneration. However, the information on such interactions is very limited. Some agronomic practices, especially proper water and nitrogen management, could reduce spikelet degeneration but the mechanism underlying remains unclear. Further research is needed to understand the cross-talk among/between phytohormones on spikelet degeneration, to reveal the physiological and molecular mechanism in which phytohormones and their interactions regulate the degeneration of spikelets, to exploit approaches to decrease spikelet degeneration and to elucidate their mechanism.